Konsep Esensialisme dalam Perspektif Pendidikan Agama Islam - Ari Supriadi; Riri Novia Sari Hasibuan; Herlini Puspika Sari (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
The essentialist school of philosophy is a school of philosophy that wants humans to return to their old culture. The emergence of this ideology was a reaction to the absolute and dogmatic symbolism of the Middle Ages. In this way, a systematic and comprehensive concept regarding humans and the universe is formed that is in accordance with the needs of the times. This essentialism assumes that education based on the core belief in flexibility in all its forms can produce views that are easily changed, easily swayed, directionless, and less stable. Therefore, education must be based on values that are stable, proven, long-term, and have values that enable a country's education to remain stable and focused. The aim of the essentialist educational philosophy is to improve the character of society through existing cultural heritage, so that later students can contribute to improving social life in the face of changing times that can damage character values. The purpose of this paper is to examine the philosophy of essentialism from the perspective of Islamic education using library research methods. Based on the research results, it is stated that essentialist schools have a view of the field of education, namely educational goals, educational curriculum, educators, students and the environment. Apart from that, there are several views that can be used as measuring tools and should be taken seriously. These are the ontological view, epistemological view and axiomatic view.